Lights, camera, action!: Using cinematographic genre in English language classes (Research, Society and Development, 2021)
This study consists of an academic activity carried out in a master's degree in Professional and Technological Education (PROFEPT) of Instituto Federal do Piauí (IFPI) in progress. The use of the short film genre in English language teaching becomes relevant as it allows the student the opportunity to practice and understand the language orally and critically. In this context, this article sought in the epistemological way to discuss the dyad education and work and their conceptions and interrelationships in professional and technological education, as well as to present a prior state of the art on the use of short films in the English language teaching in technology in contemporary society. From a qualitative perspective, this systematic literature review used as references: journals, dissertations, theses and books, found through the following databases: SciELO, Portal Capes and Google Scholar. Therefore, due to the aspects mentioned in this academic-scientific investigation, it was possible to show that the short film genre is a pedagogical strategy to promote the praxis of conversation in English language classes with students in the High School Technical Professional Education, considering contextualization and interdisciplinarity as guiding principles, thus ensuring the inseparability between theory and social practice. This research seeks to highlight the conceptions, possibilities and challenges in contemporary English language teaching, through the short film genre.